Designing Application of Augmented Reality Introduction of Hindu-Buddha Temple for Elementary School. (Case Study: Pisangan Sdn 01 Morning) - Sandfreni; Wijaya, Aurelia; Yulfitri, Alivia; Martoni, M.T, (International Journal of Psychosocial Rehabilitation, 2020)
Monotony in learning is one type of difficulty that often occurs in students, in another sense, the importance of variations in conveying lessons. Learning applied to primary schools usually uses a printed book, teacher’s explanation, and field practice. To overcome this, a learning aid was created about Hindu-Buddhist temple culture by utilizing augmented reality technology, where this technology is able to present educational information to the real world. Augmented reality technology in the world of education provides a great opportunity to improve user satisfaction and experience. Augmented reality technology combines objects in the real world with virtual objects. The output of the application displays 3D images with audio and visuals. Make it easy for students and instructors to use the application.